Pengaruh Program Berita “Sketsa Pemilu” Di TVRI Terhadap Persepsi Mahasiswa (Survei pada Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Jakarta Angkatan 2020 dan 2021) - Lukman, Alifia Syahradinar; Kurniawan, Donny (PT Literasi Nusantara Publisher, 2024)
One of the mass media programs that discusses elections is the election sketch news program. The aim of the research is to measure 1). News program